A novel deep intronic variant in ATP7B in five unrelated families affected by Wilson disease. Issue 10 (8th August 2020) - Woimant, France; Poujois, Aurelia; Bloch, Adrien; Jordi, Tabaras; Laplanche, Jean‐Louis; Morel, Hélène; Collet, Corinne
Abstract: Background: Wilson disease is an autosomal recessive metabolic disorder resulting from accumulation of excess copper especially in the liver and brain. This disease is mainly characterized by hepatic disorders and less frequently by neuro‐psychiatric disturbances. This recessive disease is due to mutation in ATP7B, which codes for an ATPase involved in copper‐transport across the plasma membrane. Molecular diagnosis of WD is positive in approximately 98% of cases. Also, in few cases, WD patients present a single deleterious mutation (heterozygous) or no mutation after sanger and NGS standard sequencing analysis of ATP7B . Therefore, in these problematic WD cases, we hypothesized that deleterious mutations reside in intronic regions of ATP7B . Methods: Complete ATP7B gene was sequenced by Next Generation Sequencing including its promoter. Results: Five unrelated families with Wilson disease shared the same novel, deep intronic NG_008806.1 (ATP7B_v001):c.2866‐1521G>A variant in ATP7B . Analysis of RNA transcripts from primary fibroblasts of one patient confirmed the deleterious impact of the intronic variant on splicing and its likely pathologic effect in this compound heterozygote. Conclusion: This discovery of a novel intronic mutation in ATP7B has improved the molecular diagnosis of WD in the French patient cohort to greater than 98%. Thus, we recommend complete sequencing of ATP7B gene, including introns, as a molecular diagnostic approach in cases of clinically confirmed WD which lack pathogenic exon or promoter variants in one or both alleles. Abstract : Unexpected intronic splicing variant in Wilson disease.